2018
DOI: 10.1080/15622975.2018.1500032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the concentrations of psychotropic drugs in HIV-infected versus HIV-negative patients: Potential implications for clinical practice

Abstract: A higher rate of sub-therapeutic antidepressant and/or antipsychotic drugs concentrations were found in HIV-infected patients. The creation of multidiscliplinary specialist teams may contribute to improving the management of such complex patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A recently published study demonstrated that clinicians tend to overestimate the impact of the inhibitory effect of ritonavir/cobicistat, resulting in the use of too low doses of psychotropic drugs in PLWH due to fear of DDIs . While ARTs are indeed among therapeutic agents with the highest potential for DDIs, they did not appear to affect escitalopram exposure, confirming previous observations .…”
Section: Discussionsupporting
confidence: 86%
“…A recently published study demonstrated that clinicians tend to overestimate the impact of the inhibitory effect of ritonavir/cobicistat, resulting in the use of too low doses of psychotropic drugs in PLWH due to fear of DDIs . While ARTs are indeed among therapeutic agents with the highest potential for DDIs, they did not appear to affect escitalopram exposure, confirming previous observations .…”
Section: Discussionsupporting
confidence: 86%
“…A misunderstanding of these concepts and of the different DDI of each antiretroviral drugs can lead to an overestimation of the risk of DDI leading consequently to sub-optimal treatment. This issue has been reported for antidepressants since a larger proportion of PLWH were shown to have sub-therapeutic antidepressants levels compared to uninfected individuals suggestive of a deliberate lower dosing as clinicians fear DDIs with antiretroviral drugs [118]. It should be highlighted that most antidepressants are metabolized by several cytochromes and therefore the magnitude of DDIs with boosted regimens tend to be mitigated.…”
Section: Current Issues When Managing Drug-drug Interactionsmentioning
confidence: 96%
“…antidepressants, and antiepileptic drug trough concentrations in our laboratory, we assessed the distribution of plasma trough CNS drug concentrations in both PLWH and HIV-negative patients using the reference ranges provided by the Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie (AGNP) guidelines. 81,82 Interestingly, we found that 64 % and 55 % of PLWH concomitantly receiving an antiretroviral and antipsychotic or antidepressant drug treatment versus 26 % and 25 % of HIV-negative patients had sub-therapeutic plasma psychotropic drug concentrations (Figure 3, difference statistically significant). Conversely, only 30 % and 28 % of PLWH and HIV-negative patients, respectively, had antiepileptic concentrations below the therapeutic targets (difference not statistically significant).…”
Section: A C C E P T E Dmentioning
confidence: 83%
“…Shaded lines represent the minimum effective atazanavir trough concentration (set at 150 ng/mL). Distribution of trough antipsychotic, antidepressant, and antiepileptic drug concentrations below, within, and above the reference ranges of the AGNP consensus guidelines 81,82 in PLWH versus HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%